Предмет: Алгебра,
автор: TimMaer
Выполнить действие (a > 0, b > 0)
Приложения:
Ответы
Автор ответа:
0
[(ab)^(1/5) - b^(1/5)] / b^(1/5) - a^(1/5) =
{[(b)^(1/5)]*(a^(1/5) - 1)} /[ b^(1/5)] - a^(1/5) =
= a^(1/5) - 1 - a^(1/5) = -1
{[(b)^(1/5)]*(a^(1/5) - 1)} /[ b^(1/5)] - a^(1/5) =
= a^(1/5) - 1 - a^(1/5) = -1
Приложения:
Похожие вопросы
Предмет: Математика,
автор: bahodirsabirov5
Предмет: Физика,
автор: ssimkina83
Предмет: Українська література,
автор: davil432122
Предмет: Физика,
автор: 0636041158
Предмет: Литература,
автор: Torment